Weapons and technologies of war in the context of cultural and historical development of humanity - Tormakhova, (Ukrainian Cultural Studies, 2022)
The historical and cultural development of mankind is a time not only of progress and peace. Throughout human history, there have been many wars in which weapons, protective equipment, and so on have been developed. Transformation of military equipment is taking place in the direction of increasing range, the strength of the enemy's defeat. The "evolution" of weapons is inextricably linked with the development of science and technology. The development of weapons is closely linked to the formation of military groups. This type of activity, which is carried out throughout life, contributes to the development of specific skills and abilities in the use of weapons, fighting, which is virtually inaccessible to ordinary citizens. Professionalization of military activity is aimed at forming the physical and psychological readiness to destroy the enemy, the ability to bear the losses of allies and more. Often, inventions discovered for peaceful purposes become the basis for the creation of means of destruction. The formation of various weapons involves the creation of opportunities to exceed the possibilities of protection against them. In this way, the dominant principle is to achieve the most remote nature of the fighting. This process is accompanied by the creation of weapons of mass destruction, the use of which is easier for the consciousness of the soldier than a form of contact. An integral part of active hostilities are the means of psychological influence on the enemy. Military action is not limited to the use of weapons, which are carried out for a specific strategic purpose, which is realized through combat tactics. All wars included the permanent practice of psychological influence on the enemy. It could be related to the appearance of the enemy, his behavior on the battlefield. At the same time, the introduction of forms of struggle related to the spread of misinformation, undermining the belief in ideals, etc., was equally important. Such forms of struggle have become especially relevant at a time when access to information has become much easier. Due to the promotion of certain content in the priority media channels, the recipient has a significant impact.
Keywords: war; culture; weapons; technologies; distance